Development of filtration system for the collection of soaking water during bedak sejuk preparation - Nurhasniza Ibrahim; Noorhisham Tan Kofli (Penerbit Universiti Kebangsaan Malaysia, 2019)
“Bedak Sejuk” or fermented rice powder is a traditional cosmetic product used by locals that is made from fermented rice. To start the process, the rice grains are soaked in water at 1:1 (w:v) ratio and continuously soaked until the rice gains fully dissolved into flour paste slurry. The soaking water was discarded at end of the fermentation process although it is believed valuable active components still exist in the water. Thus, the aim of the present study is to develop filtration system to collect the soaking water and to analyze active components presence. Local rice grains were soaked in the water in a container and within 14 days interval, the soaking water was replaced. The soaking water collected was then filtered using muslin cloth, followed by membrane filter size of 0.45 and 0.20μm. The filtered soaking water was analyzed for amino acid analysis using HPLC. Sample (0.1 ml) was poured onto the nutrient agar plate for microbial growth to determine the effectiveness of the filtration system. Based on these observations, it can be concluded that the rice soaking water during bedak sejuk preparation content were rich in amino acids (15 types of amino acids detected) with the highest concentration were lycine, glutamic acid and arginine – 0.11, 0.12 and 0.16% respectively. After the filtration using 0.20μm, no microbial growth detected suggested that it can be applied directly onto the skin as organic cosmetic product that benefits the skin.